Strong Association Between Birth Month and Reproductive Performance of Vietnamese Women - HUBER, SUSANNE (2009)
Epidemiological studies on premodern and modern Western societies indicate that birth season may influence female reproduction. Nothing is known, however, about this effect in developing economies. Many of the latter are characterised by tropical climates with a rainy season associated with lower food availability and a greater prevalence of infectious diseases. We therefore predict that an association between birth month and reproductive output, if it exists, should be related to the rainy season. To test this prediction, we analysed census data of Vietnam obtained from IPUMS-International (Vietnam 1999 Population and Housing Census). Based on 493,853 women born between 1950 and 1977 and thus aged 22 to 49 years, we found that the time series of mean offspring count per month of birth has a highly significant period of 12 months (power = 46.871, P < 0.00001). Our results further indicate that the 12-month periodic signal has a maximum in July and a minimum in January. Accordingly, the peak corresponds to birth during the rainy season, the low if the third pregnancy month concurs with the rainy season. The month of birth is therefore clearly associated with the later reproductive performance of Vietnamese women, strongly supporting the assumption that environmental and maternal conditions during early development exert long-term effects on reproductive functioning. Provided the rainy season adversely affects developmental processes due to inadequate food and/or high infection risk, the association reported here points to a critical period of reproductive development during early pregnancy.